Major Shareholder Tunneling and Corporate Earnings Management: A Narrative Review of China’s Non-Financial Listed Firms - Wang, Xinyao (Exploring Science Academic Conference Series, 2026)
Major shareholder tunneling and corporate earnings management are two pervasive issues in modern capital markets, particularly in emerging economies like China. Tunneling refers to the expropriation of firm resources by controlling shareholders for their private benefits, while earnings management involves the manipulation of financial reports to mislead stakeholders or influence contractual outcomes. Although both phenomena have been extensively studied separately, their interrelationship has received less systematic attention. This review synthesizes existing literature on how tunneling affects earnings management, how this relationship varies across governance structures, and what economic consequences arise from their joint occurrence. The findings reveal three main conclusions. First, tunneling and earnings management are positively correlated; tunneling creates incentives for concealment via earnings management, and earnings management-induced information opacity further facilitates tunneling. Second, governance mechanisms significantly moderate this relationship—the positive association is weaker in firms with stronger internal governance and better external monitoring. Third, the joint occurrence of tunneling and earnings management produces severe negative consequences, including reduced firm value, lower information quality, higher stock price crash risk, and dual damage to minority shareholders. This review contributes to theory by integrating tunneling and earnings management literature into a coherent framework and to practice by offering references for regulatory policy design, corporate governance improvement, and investor risk identification.